Steady-state analysis of the stochastic Beverton-Holt growth model driven by correlated colored noises. (May 2022) - Yu, Xingwang; Ma, Yuanlin
Abstract: In this paper, we investigate a single population growth model with Beverton-Holt function, which is driven by cross-correlation between multiplicative and additive colored noises. Firstly, using approximate Fokker-Planck equation, the stationary probability distribution of the model is obtained, and then its the shape structure is discussed in detail. In addition, the influence of noise characteristics on mean, variance and skewness is studied numerically. Finally, an explicit expression of the mean first passage time is given by using the steepest-descent approximation. It is found that: (i) the P-bifurcation occurs when the two noises are positively correlated or zero correlated, but not in the case of negative correlation; (ii) a strong negative correlation degree and correlation time can promote population growth, while the strong positive correlation degree plays an opposite role; (iii) the noise enhanced stability induced by multiplicative noise is different from that induced by the additive one. Highlights: A Beverton-Holt growth model driven by correlated colored noises is proposed. The shape structure of SPD and the influence of noise characteristics on mean, variance and skewness are discussed. P-bifurcation occurs in the case of positive or zero correlation, but not in the case of negative correlation. The noise enhanced stability induced by multiplicative noise is different from that induced by the additive one.